The Role of Internal Limiting Membrane as a Biomarker in the Evolution of Myopic Traction Maculopathy - Fang, Dong; Su, Jindi; Chen, Lu; Zhang, Shaochong (Frontiers in Medicine, 2022)
Purpose: To describe the longitudinal structural changes of myopic traction maculopathy (MTM) based on optical coherence tomography (OCT) and to detect biomarkers in the evolution of MTM. Methods: A retrospective study was conducted on patients with MTM as defined by OCT. A minimum follow-up of 6 months was necessary for study inclusion. The effects of comprehensive OCT-based structure on the evolution of MTM, the progression rates, and resolution rates of MTM were evaluated. Results: A total of 120 eyes (120 patients) were included with an average follow-up of 15.4 months. During the follow-up, MTM progressed in 32 eyes (26.67%). The most common pattern of progression observed was the increased extent of retinoschisis in 12 eyes. The multivariate analysis showed that the presence of MTM progression had a significant correlation with internal limiting membrane (ILM) detachment and retinoschisis involved the entire macula at baseline. Five eyes (4.17%) experienced MTM resolution, of which 2 eyes developed disruptions of detached ILM, two eyes developed disruptions of epiretinal membrane, and one eye developed partial posterior vitreous detachment. Eyes with foveal detachment showed the highest progression rate (41.67%) and highest resolution rate (16.67%) compared to the eyes with other foveal complications. Conclusion: ILM detachment is a risk factor for MTM progression and MTM resolution can occur after ILM disruption. These suggest that ILM may play an important role as a biomarker in the evolution of MTM.